2016
DOI: 10.1093/icvts/ivw041
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve replacement with sutureless prosthesis: better than root enlargement to avoid patient–prosthesis mismatch?

Abstract: Although the sutureless valve patients received significantly more concomitant procedures, all operation-associated times were significantly shorter. Despite sutureless valve patients being older, the 30-day mortality and survival rates were comparable in the two groups. Since the indexed EOA was only slightly lower and the incidence of severe PPM was not significantly higher in the sutureless valve patients, we conclude that sutureless valve implantation is an alternative to conventional ARE to treat a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 10 publications
4
56
0
5
Order By: Relevance
“…We could not detect a time benefit in terms of reduced CPB or aortic clamp time favoring one RDV type over the other. Both RDV have been repeatedly linked to a significant reduction in CPB and aortic clamp time when compared with conventional bioprosthetic AVR [5,6,8,9,19,21], with CPB and aortic cross-clamp times being similar to our report. For example, the Intuity RDV facilitated a 24% reduction in aortic cross-clamp time compared with conventional AVR in the CANDENCE-MIS [8]; and the TRANSFORM investigators reported a clinically meaningful reduction of CPB and aortic clamp time, especially for patients with combined AVR and CABG procedures when compared with the corresponding results of The Society of Thoracic Surgeons Adult Cardiac Surgery Database [5].…”
Section: Commentsupporting
confidence: 88%
See 2 more Smart Citations
“…We could not detect a time benefit in terms of reduced CPB or aortic clamp time favoring one RDV type over the other. Both RDV have been repeatedly linked to a significant reduction in CPB and aortic clamp time when compared with conventional bioprosthetic AVR [5,6,8,9,19,21], with CPB and aortic cross-clamp times being similar to our report. For example, the Intuity RDV facilitated a 24% reduction in aortic cross-clamp time compared with conventional AVR in the CANDENCE-MIS [8]; and the TRANSFORM investigators reported a clinically meaningful reduction of CPB and aortic clamp time, especially for patients with combined AVR and CABG procedures when compared with the corresponding results of The Society of Thoracic Surgeons Adult Cardiac Surgery Database [5].…”
Section: Commentsupporting
confidence: 88%
“…For example, the Intuity RDV facilitated a 24% reduction in aortic cross-clamp time compared with conventional AVR in the CANDENCE-MIS [8]; and the TRANSFORM investigators reported a clinically meaningful reduction of CPB and aortic clamp time, especially for patients with combined AVR and CABG procedures when compared with the corresponding results of The Society of Thoracic Surgeons Adult Cardiac Surgery Database [5]. Similarly, a 20% to 40% reduction of CPB time and aortic clamp time was observed with the Perceval RDV for isolated or combined RDAVR procedures compared with conventional AVR [9,13,19]. Nonetheless, the potential benefit of RDV-facilitated reduction of CPB and aortic clamp time on hard clinical endpoints remains to be proven in future clinical trials for both isolated and combined procedures.…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…Several authors described their results with the use of Perceval S bioprostheses in high risk patients, with minimally invasive approach or in combined surgery [2][3][4][5][6][7][8][9][10]. However no one describes the experience of combined Perceval S aortic valve replacement with concomitant myocardial revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Recently, sutureless valves have also been proposed as an alternative to aortic root enlargement; they have an acceptable safety profile while allowing for a larger valve size to be inserted. 22 Another meta-analysis showed that stentless valves provide larger effective orifice areas, lower mean gradient and greater ventricular mass regression. 23 In addition, techniques such as aortic root enlargement to allow for the insertion of larger bioprosthetic valves are occasionally considered for patients at risk of severe PPM.…”
Section: Pre-surgical Considerationsmentioning
confidence: 99%